2007
DOI: 10.1016/j.febslet.2007.12.024
|View full text |Cite
|
Sign up to set email alerts
|

LPS‐induced Toll‐like receptor 4 signalling triggers cross‐talk of apoptosis signal‐regulating kinase 1 (ASK1) and HIF‐1α protein

Abstract: Toll-like receptor 4 (TLR4) is required for recognition of lipopolysaccharide (LPS) of Gram-negative bacteria and induction of the innate immune response to them. Nevertheless, the involvement of some crucial pathways in TLR4 signalling is poorly understood. Here, we report that LPS-induced TLR4 signalling triggers cross talk of HIF-1a and ASK1 in THP-1 human myeloid monocytic leukaemia cells. Both pathways are activated via redox-dependent mechanism associated with tyrosine kinase/phospholipase C-1c-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
111
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 62 publications
(121 citation statements)
references
References 28 publications
(43 reference statements)
10
111
0
Order By: Relevance
“…Since TLR7/8 are associated with the MyD88 adaptor, which is known to promote generation of ROS and RNS [2,6,13], we hypothesised that redox-and RNS-dependent mechanisms may be employed in TLR7/8-induced accumulation of HIF-1a protein. Signaling pathways induced by some TLRs, including TLR7/8, lead to the activation of tyrosine kinases, such as Bruton's tyrosine kinase (Btk) [14], that interact with MyD88, which binds to the TLR TIR domain.…”
Section: Tlr7/8 Trigger Hif-1a Accumulation Via Redox-and Rns-dependementioning
confidence: 99%
See 4 more Smart Citations
“…Since TLR7/8 are associated with the MyD88 adaptor, which is known to promote generation of ROS and RNS [2,6,13], we hypothesised that redox-and RNS-dependent mechanisms may be employed in TLR7/8-induced accumulation of HIF-1a protein. Signaling pathways induced by some TLRs, including TLR7/8, lead to the activation of tyrosine kinases, such as Bruton's tyrosine kinase (Btk) [14], that interact with MyD88, which binds to the TLR TIR domain.…”
Section: Tlr7/8 Trigger Hif-1a Accumulation Via Redox-and Rns-dependementioning
confidence: 99%
“…These data suggest that TLR7/8-dependent accumulation of HIF-1a protein is achieved via redox-and RNS-dependent mechanisms. This indicates that membrane-associated TLR4 and endosomal TLR7/8 utilize different mechanisms for HIF1a accumulation, since the ASK1-p38 pathway does not play any role in R848-induced HIF-1a accumulation but is crucial in the case of TLR4 signaling [6]. In addition, we have shown that HIF-1a knockdown with siRNA in THP-1 myeloid macrophages leads to a depletion of ATP, a decrease in R848-induced production of interleukin-6 (IL-6) and tumour necrosis factor alpha (TNFa), and a significant increase in caspase-3 activity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations